Caffeine ingestion enhances perceptual responses during intermittent exercise in female team-game players. Issue 4 (16th February 2016) - Ali, Ajmol; O'Donnell, Jemma; Von Hurst, Pamela; Foskett, Andrew; Holland, Sherina; Starck, Carlene; Rutherfurd-Markwick, Kay
Abstract: We examined the influence of caffeine supplementation on cognitive performance and perceptual responses in female team-game players taking low-dose monophasic oral contraceptives of the same hormonal composition. Ten females (24 ± 4 years; 59.7 ± 3.5 kg body mass; 2–6 training sessions per week) took part in a randomised, double-blind, placebo-controlled crossover-design trial. A 90-min intermittent treadmill-running protocol was completed 60 min following ingestion of a capsule containing either 6 mg  kg −1 anhydrous caffeine or artificial sweetener (placebo). Perceptual responses (ratings of perceived exertion (RPE), feeling scale (FS), felt arousal scale (FAS)), mood (profile of mood states (POMS)) and cognitive performance (Stroop test, choice reaction time (CRT)) were completed before, during and after the exercise protocol, as well as after ~12 h post exercise. Caffeine ingestion significantly enhanced the ratings of pleasure ( P  = 0.008) and arousal ( P  = 0.002) during the exercise protocol, as well as increased vigour (POMS; P  = 0.007), while there was a tendency for reduced fatigue (POMS; P  = 0.068). Caffeine ingestion showed a tendency to decrease RPE ( P  = 0.068) and improve reaction times in the Stroop ( P  = 0.072) and CRT ( P  = 0.087) tests. Caffeine supplementation showed a positive effect on perceptual parameters by increasing vigour and a tendency to decrease fatigue during intermittent running activity in female games players taking low-dose monophasic oral contraceptive steroids (OCS).